Optimising soil disturbance and mulch attenuation for erosion and runoff control in asparagus crops - Niziolomski, Joanna (Cranfield University, 2014)
Exposure of bare soil for long periods and onsite compaction create soil and water problems in asparagus production. This project aims to develop a cost effective and practical runoff and soil erosion management system. Two field trials (Phase 1 running from April - July 2012 and Phase 2 running from May - November 2013) tested different combinations of shallow soil disturbance (SSD) and mulch (straw and compost) application for soil erosion control. Cranfield University’s soil bin was used to test the effect of different tine configurations on soil disturbance. The results of this research corroborated observations that asparagus production can result in levels of unsustainable soil loss that will contribute to the degradation of the existing soil resource. The field trials demonstrated that a straw mulch applied at 6 t ha- 1 significantly improved key performance indicators (KPIs, i.e. runoff initiation, volume and rate; total soil loss; sediment concentration; total oxides of nitrogen; orthophosphate-P; and sediment-bound P) as compared with the Non-SSD Control. In general, SSD (irrespective of tine configuration) was ineffective at improving key performance indicators as compared with the Non-SSD Control. In the soil bin work, different tine configurations generated varying degrees and extent of SSD, with the modified para-plough giving the greatest soil disturbance for the least draught force. However, the differences in SSD observed in the soil bin had no effect on the KPI’s tested in the Phase 2 field trial. The effective treatments observed in the field trials only yielded cost savings to the farmer/grower when a high level of soil loss occurred. This research highlights the need to develop erosion control measures in asparagus fields, with wider implications to other row crops. However caution is needed, given the observed variation in effectiveness and reliability of in-field mitigation measures, especially during ‘extreme’ rainfall events.
Keywords: Compaction; straw; compost; infiltration; tillage